Americans and policymakers underestimate endorsement for the most popular climate solution narrative, combining personal and political action - Gregg Sparkman; Joel Ginn; Shahzeen Z. Attari; Elke U. Weber (Communications Earth & Environment)
Abstract A wide variety of existing narratives describe how we might address climate change. Which of these approaches is popular among the American public? Do the general public and their elected officials accurately perceive which climate solutions are popular? We assess personal endorsement and perceptions of public support in national representative samples of the U.S. public (N = 1500) and local-level U.S. policymakers (N = 500). Proactive narratives, like ones advocating for both personal behavior and policy action, are widely endorsed, but both the public and policymakers greatly underestimate their popularity (a case of pluralistic ignorance), especially for narratives calling for systemic change. Greater endorsement of these narratives corresponded to greater willingness to take personal and political actions and support climate policy. We also find experimental exposure to some climate narratives (N = 2060) may increase participants’ behavioral intentions and policy support, suggesting which narratives are spread in popular media is important to help address climate change.